Petrographie Des Volcanites Et Plutonites De La Partie Sud Du Sillon Volcano-Sedimentaire De Toumodi-Fetekro (Cote D’ivoire) - Inza, Coulibaly; Nicaise, Kouamelan Alain; Chérubin, Djro Sagbrou; Yacouba, Coulibaly (European Scientific Journal, ESJ, 2017)
The southern part of Toumodi-Fètêkro greenstone belt is located in the Center - Southeast of Ivory Coast. Petrographic study of volcanic and plutonic rocks shows three units. The first unit is composed of basaltic to rhyolitic lavas which imply effusive character. Then we have volcanosedimentary unit composed of pyroclastic formations (lapilli tuff, breccia, ash deposit and ignimbrites) and the pillow-lavas. Indeed, the presence of this last shows clearly that an explosive volcanism and a submarine effusive volcanism have occurred during during the setting of Toumodi-Fètêkro belt. Plutonic unit is constituted of gabbroic to granitic rocks. Sericite, chlorite, epidote observed in these rocks are consistent with the impacts of greenschist facies metamorphism. The rocks of the southern part of the Toumodi-Fètêkro greenstone belt are formed in a subduction context rather than in oceanic plateaus context because of the old inheritance, sometimes of Archean age, found somewhere in theBirimiandomain. The lithologies of the southern part of Toumodi-Fètêkro meet elsewhere in the other Birimian greenstone belts. Also, these lithologies are affected by a hydrothermal alteration due to the abundant veins of quartz, carbonates, sericite, chlorite, epidote, sulphides and oxides. However, volcanic show in some places amphibolit facies metamorphism.